2012
DOI: 10.1111/j.1939-3938.2012.01138.x
|View full text |Cite
|
Sign up to set email alerts
|

Information sharing between the National Health Service and criminal justice system in the United Kingdom

Abstract: Offenders with mental health problems often have complex and interrelated needs which separately challenge the criminal justice system (CJS) and National Health Service (NHS) in the United Kingdom (U.K.). Consequently, interagency collaboration and timely information sharing are essential. This study focused on the sharing of information about people with mental health problems in contact with the CJS. Questionnaires were distributed to a range of health and criminal justice personnel. The results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
0
6
0
1
Order By: Relevance
“…Reference to the offender health pathway suggests the existence of a seamless delivery and experience of care. However, evidence (both from this project and wider research, for example Williams, 2009;Lennox et al, 2010Lennox et al, , 2012 points to the contrary, organisations continue to work in silos; or where there is evidence of inter-agency working, episodes of care during contact with the criminal justice system are themselves treated as silos with minimal if any links with the next part of the pathway. For example, the provision of healthcare at police stations, issues around custody diversion and support for offenders with mental health problems at court and prison healthcare are in the main treated as discrete periods within which care must be provided, issues considered and problems resolved, but between which there are few links made (Peay, 2007(Peay, , 2010Dyer, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Reference to the offender health pathway suggests the existence of a seamless delivery and experience of care. However, evidence (both from this project and wider research, for example Williams, 2009;Lennox et al, 2010Lennox et al, , 2012 points to the contrary, organisations continue to work in silos; or where there is evidence of inter-agency working, episodes of care during contact with the criminal justice system are themselves treated as silos with minimal if any links with the next part of the pathway. For example, the provision of healthcare at police stations, issues around custody diversion and support for offenders with mental health problems at court and prison healthcare are in the main treated as discrete periods within which care must be provided, issues considered and problems resolved, but between which there are few links made (Peay, 2007(Peay, , 2010Dyer, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested, by case leaders and YFS teams, that there should be more direct communication and interaction between YFS teams and care teams. There is existing research that supports the idea of having contact between mental health teams and those staff working directly with people, including in prisons (Lennox, Mason, McDonnell, Shaw, & Senior, 2012) and schools (Rothi & Leavey, 2006). However, this was the first research project to identify this need within a youth justice residence.…”
Section: Role Claritymentioning
confidence: 99%
“…The work done by Lennox et al (2012) in establishing a model of information-sharing for adult prisoners in the United Kingdom is reflected in this current research project. Lennox et al (2012) identified that prison staff want information about mental health history, while mental health staff want information about risk and sentences. Their finding (that mental health teams usually received more information than the prison staff received) was similar to the current findings.…”
Section: Contrast With the Literaturementioning
confidence: 99%
“…Knowledge transfer between systems is often problematic and the assumptions and values that guide behaviour within each system differ (Hean et al, 2009). This is illustrated by the alternative perspectives held by different actors on the management of risk versus rehabilitation when working with offenders or differing views on what constitutes offender confidentiality and appropriate information sharing (Lennox, Mason, McDonnell, Shaw & Senior, 2012).…”
Section: Introductionmentioning
confidence: 99%